Suppressor Analysis Uncovers That MAPs and Microtubule Dynamics Balance with the Cut7/Kinesin-5 Motor for Mitotic Spindle Assembly in Schizosaccharomyces pombe. Issue 1 (1st January 2019) - Yukawa, Masashi; Yamada, Yusuke; Toda, Takashi
Abstract: The Kinesin-5 motor Cut7 in Schizosaccharomyces pombe plays essential roles in spindle pole separation, leading to the assembly of bipolar spindle. In many organisms, simultaneous inactivation of Kinesin-14s neutralizes Kinesin-5 deficiency. To uncover the molecular network that counteracts Kinesin-5, we have conducted a genetic screening for suppressors that rescue the cut7-22 temperature sensitive mutation, and identified 10 loci. Next generation sequencing analysis reveals that causative mutations are mapped in genes encoding α-, β-tubulins and the microtubule plus-end tracking protein Mal3/EB1, in addition to the components of the Pkl1/Kinesin-14 complex. Moreover, the deletion of various genes required for microtubule nucleation/polymerization also suppresses the cut7 mutant. Intriguingly, Klp2/Kinesin-14 levels on the spindles are significantly increased in cut7 mutants, whereas these increases are negated by suppressors, which may explain the suppression by these mutations/deletions. Consistent with this notion, mild overproduction of Klp2 in these double mutant cells confers temperature sensitivity. Surprisingly, treatment with a microtubule-destabilizing drug not only suppresses cut7 temperature sensitivity but also rescues the lethality resulting from the deletion of cut7, though a single klp2 deletion per se cannot compensate for the loss of Cut7. We propose that microtubule assembly and/or dynamics antagonize Cut7 functions, and that the orchestration between these two factors is crucial for bipolar spindle assembly.